A Study on Hindrance of Customs Procedures to Taiwan’s Development of Free Trade Zones - Cho, Cheng-Chung; Yang, Fu- Chiang (IJRDO - Journal of Business Management, 2017)
This study investigated the hindrance of customs procedures to the development of free trade zones in Taiwan, attempted to identify the hindrances and proposed solutions through literature reviews and field research. Through literature reviews and field research, this study found that: a. customs procedures impede the liberalization of international logistics in free trade zones., b. the coexistence of business in existing development areas and same business in free trade zones impedes customs management; c. customs is inflexible in thinking and rules and is not easily subject to autonomous management; d. unsimplified customs procedures are one of the major obstacles to the development of free trade zone in Taiwan; e. the Customs Administration, the Ministry of Transportation and Communications, and non-governmental enterprises have different attitudes towards autonomous management of security guards and audit mechanism.